الإضراب بین الشریعة والقانون - دراسة مقارنة - - معیوة, یاسین; رحماني, بلخیر; - رزوق, عبد الر ا زق (University of Eloued-جامعة الوادي, 2016)
تناولت هذه الد ا رسة الإض ا رب د ا رسة مقارنة بین الشریعة الإسلامیة والقانون الوضعي، هادفة إلى بیان أ ري الفقه الإسلامي والقانون الوضعي، وقد تم الوقوف على ماهیته من تعریفه وأنواعه وشروطه ومقوماته وبیان حكمه في الشریعة الإسلامیة والقانون الوضعي، وكذلك بیان آثاره على الفرد والمجتمع والدولة؛ فتبین أن حق الإض ا رب حق أصیل ومكفول في المواثیق والعهود الدولیة كما هو كذلك في الوثائق الدستوریة الج ا زئریة، وظهر أیضا أن قواعد الشریعة الإسلامیة ومقاصدها العامة تحث على تحصیل الحقوق وتحقیق العدالة لعموم المكلفین، ومن ذلك إض ا رب العاملین عن العمل أو إض ا رب المساجین أو غیرهم عن الطعام للمطالبة بحقوقهم، ومن خلال الوقوف على هذه المحددات وما یتعلق بالإض ا رب؛ أمكن القول بأن الإض ا رب لیس مقصودا لذاته وإنما لكونه وسیلة موصلة إلى حاجات الإنسان، وبالتالي فهو مشروع إذا روعیت شروط القیام بهThis research paper addresses "the strike" as a comparative study between Islamic Sharia'a and the positive law, which aims at clarifying the opinions of both the Sharia'a and the positive law, this has focused on the essence of the strike, its definition, types, conditions, fundamentals as well as its statement in the Islamic Sharia'a and the positive law, nedless to say the effects on the individual as well as the society and the country. As a result we have discovered that the right of the strike is principal and guaranteed in the international statements and laws which is the same in the Algerian constitutional documents, it turned out also that even the Islamic Sharia'a and its general purposes urges and encourages people to ask for their rights and achieve justice for those involved, including workers strike in their work and food strike by prisoners in the jail or any other to ask for their rights. By covering all the aspects and strike-related issues, we can now say that the strike is not meant for being a strike, but it's meant for being a way to achieve some human needs and as a result it is a legal action as soon as it still under the legal terms..
شريعة وقانون